Cascading verification initiated by switching attacks through compromised digital relays. Issue 3 (19th March 2022) - Yamashita, Koji; Yang, Zhiyuan; Ten, Chee‐Wooi; Kar, Soummya; Ginter, Andrew
Abstract: Attackers are able to enumerate all devices and computers within a compromised substation network. Digital relays deployed in the substation are the devices with IP addresses that can be discovered in the process of trial‐and‐error search. This paper is concerned with studies of cyberattacks manipulating digital relays to disruptively disconnect the associated breakers. The plausible enumeration of such disruptive attack for each relay in a substation is verified with the dynamic simulation studies with the special protection system for frequency, voltage, and rotor angle stability. A pertinent approach with smaller scale contingency analysis results is proposed to reduce the enormous computation burden. The devised enumeration reduction method is evaluated using IEEE test cases. The proposed method provides an extensive enumeration strategy that can be used by utility engineers to identify the pivotal relays in the system and can be further strengthened with security protection.